LEGAL FOUNDATIONS OF PARLIAMENTARY ACTIVITY IN THE REPUBLIC OF UZBEKISTAN (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the legal foundations of parliamentary activity inthe Republic of Uzbekistan within the context of ongoing constitutional reforms and thedevelopment of democratic governance. Particular attention is given to the principle ofseparation of powers, its theoretical underpinnings, and its practical implementation inthe national system of state authority. The study analyzes the role of Parliament (OliyMajlis) as a central institution in ensuring checks and balances among the branches ofgovernment.The article also explores the organizational and legal framework of the Parliamentas defined in the updated Constitution of the Republic of Uzbekistan, highlightingrecent changes aimed at strengthening parliamentary effectiveness and accountability.Special emphasis is placed on the core functions of Parliament, including its legislativerole in law-making, its oversight (control) function over the executive branch, and itsrepresentative function in expressing the will and interests of the people.
Keywords: Constitution; Parliament; Oliy Majlis; House of Commons; Senate; legislation; control; representation